The European Union and Regional gender equality agendas: Wales in the shadow of Brexit. Issue 9 (2nd September 2021) - Minto, Rachel; Parken, Alison
ABSTRACT: This article explores what the UK's European Union membership has meant for the development of a distinctive, substate equalities agenda in Wales. An analysis of interview data through the lens of feminist institutionalism reveals European Union membership as integral to the emergence of Wales' approach to gender equality, with Welsh equality advocates using access to European Union norms and funding to establish and legitimize more progressive institutions to advance equality, overcoming domestic resistance and gatekeeping. In turn, research exposes structural risks for Wales' equalities agenda post-Brexit. Recent equality-related activity in Wales partially mitigates against post-Brexit risks, although vulnerabilities remain.